Effect of Kaempferia galanga L. on in vitro nutriens digestibility, ruminal fermentation and methane production - Kurniawati, Asih; Widodo, Widodo; Artama, Wayan Tunas; Yusiati, Lies Mira (2016)
In vitro batch culture technique was used to evaluate the effect of Kaempferia galanga L. on nutrient digestibility, ruminal fermentation and methane production. Dry powder of Kaempferia galanga L. was added to substrate Perisetum hybride, rice bran, wheat pollard in ratio 60:20:20 (DM basis). Based on the final concentration of essential oil in the fermentation media i.e. 0, 25, 50, 75 and 1100 mg/L. Serum bottles, containing 700 mg of substrate, in amount of Kaempferia galanga L. dry powder according to treatments and 70 ml of buffered rumen fluid, were incubated at 39°C for 24 h. At the end of incubation, residual feed were collected for nutrients digestibility determination, gas and methane production, VFA and ammonia concentration, microbial nitrogen, protozoa number also pH in the fermentation media were recorded. Dry matter, organic matter and crude protein digestibility as well as microbial protein synthesis, and activity of carboxy methyl celullase were not affected by Kaempferia galanga L. addition. Total gas production and protozoa number in treatments were higher than control (P<0.01) and (P<0.05) respectively. Whereas methane concentration was lower than control (no Kaempferia galanga addition) (P<0.01), suggesting thaht inclusion of Kaempferia galanga L. in diet reduce methane production and have no detrimental effect on ruminal feed fermentation.